2022
DOI: 10.3390/biomedicines10071700
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in the Risk of Cardiovascular Disease and Identification of Risk Factors Using AIP and Castelli Atherogenicity Indicators in Patients with PCOS

Abstract: Polycystic ovarian syndrome (PCOS) is one of the most common endocrinopathies in females of reproductive age and may affect 5–14% of women. In women with PCO syndrome, metabolic disorders such as insulin resistance, hyperinsulinemia, obesity, diabetes mellitus, and other elements of metabolic syndrome may occur. Patients with PCOS often have overweight and obesity, especially abdominal obesity, which is one of the risk factors for developing atherosclerosis. The atherogenicity indicators of AIP (atherogenic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Furthermore, epidemiological studies linked low serum potassium to a significant CVDs risk. Concerning this, Nawrocka-Rutkowska et al [14] confirmed through a clinical study the positive correlation between oxidative stress markers and the occurrence of CV complications in PCOS women. They proposed AIP and Castelli Index as atherogenicity additional indicators to assess the risk of cardiometabolic diseases in PCOS in order to rapidly identify risk groups among this population.…”
mentioning
confidence: 80%
“…Furthermore, epidemiological studies linked low serum potassium to a significant CVDs risk. Concerning this, Nawrocka-Rutkowska et al [14] confirmed through a clinical study the positive correlation between oxidative stress markers and the occurrence of CV complications in PCOS women. They proposed AIP and Castelli Index as atherogenicity additional indicators to assess the risk of cardiometabolic diseases in PCOS in order to rapidly identify risk groups among this population.…”
mentioning
confidence: 80%
“…PCOS is a condition where metabolic disorders are estimated to coexist in 75% of women with PCOS of a proper weight, and in 90% of obese women with PCOS. Fifty percent of them progress to metabolic syndrome, which refers to impaired glucose tolerance, hypertension, dyslipidemia, central adiposity, and CVD [ 25 ]. Insulin resistance contributes to CVD among other metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS should be considered an important CVD risk factor that is associated with insulin resistance, which occurs independently of obesity. [ 25 ]. Hiperinsulinemia exacerbates the hyperandrogenism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to date only a few studies have used AIP indicators in woman with PCOS to analyze the risk of cardiometabolic disease. We found one study that examined the values of the HOMA-IR, Castelli Index, and AIP in PCOS [ 42 ]. Nawrocka-Rutkowska et al highlights that the Castelli index and AIP are useful additional parameters to determine the risk of cardiometabolic disease in PCOS patients, especially with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%